The Islamic Social Finance in Poverty Alleviation: R Bibilioshiny Method Approach - Birjaman, Muhammad Iqbal; Ismail, Nurizal; Mahfudz, Shaifurrokhman (University of Darusssalam Gontor, 2023)
The concept of Islamic social finance has gained significant attention in recent years as a tool for poverty alleviation. Islamic social finance refers to the use of Islamic financial instruments to address social and economic issues, including poverty, through zakat, infaq, shadaqah, and waqf. This research explores the application of Islamic social finance for poverty alleviation through the case study of the R Bibilioshiny program. Researchers conduct quantitative methods for data collection, primarily utilizing the Scopus database with the keyword